Towards the synthesis of the ABC fragment of Pectenotoxin-4 - Yang, X (2016)
This thesis details the optimisation and development to the synthesis of the ABC fragment of pectenotoxin-4, a 26-membered macrolide marine natural product bearing 19 stereogenic centres, three tetrahydrofuran rings, one spiroketal and one bicyclic ketal. Introduction This section briefly discusses the isolation, structure elucidation, and biological activity of penctenotoxins, along with a review of previous synthetic efforts on the pectenotoxin family, especially the ABC fragment. It also summarises our group’s work in pursuing the total synthesis of this compound. Results and Discussion This section details synthetic efforts to improve the overall yield of the ABC fragment. In particular, it contains the optimisation of a low yield Carreira alkynylation reaction and a revised protecting group strategy to allow orthogonal deprotection on the ABC fragment for further elaborations. The revised route for the ABC fragment of pectenotoxin-4 contains 21 longest linear steps (27 steps in total) from D-mannitol with an overall yield of 2.1% (on average 83% per step).